2015
DOI: 10.1371/journal.pone.0137823
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the TP53 Pathway in Native Americans Strongly Suggest Adaptation to the High Altitudes of the Andes

Abstract: The diversity of the five single nucleotide polymorphisms located in genes of the TP53 pathway (TP53, rs1042522; MDM2, rs2279744; MDM4, rs1563828; USP7, rs1529916; and LIF, rs929271) were studied in a total of 282 individuals belonging to Quechua, Aymara, Chivay, Cabanaconde, Yanke, Taquile, Amantani, Anapia, Uros, Guarani Ñandeva, and Guarani Kaiowá populations, characterized as Native American or as having a high level (> 90%) of Native American ancestry. In addition, published data pertaining to 100 persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…Three other genes, SP100 , DUOX2 , and CLC were identified for the first time in a high-altitude context in the present study. These genes are part of the TP53 pathway, already indicated as a potential candidate to be under natural selection in high altitude populations 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other genes, SP100 , DUOX2 , and CLC were identified for the first time in a high-altitude context in the present study. These genes are part of the TP53 pathway, already indicated as a potential candidate to be under natural selection in high altitude populations 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jacovas et al . 19 using the candidate gene approach inferred that a combination of some derived and ancestral alleles of USP7, LIF and MDM2 genes, all three in the TP53 pathway, could have been essential for the successful establishment of Native American populations in the Andean highlands.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also identified 14 miRNAs were differentially expressed genes in heart and enriched in the p53 signaling pathway, of which 13 miRNAs are downregulated in heart. It was reported that alleles of ubiquitin specific peptidase 7 (USP7), interleukin 6 family cytokine (LIF), and murine double minute2 (MDM2) were selected for in relation to harsh environmental variables related to high altitude ( Jacovas et al, 2015 ). The widespread of differentially expressed miRNAs targeting the p53 pathway gene indicated the potential involvement of p53 pathway in high altitude adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from plasma, glycerolized red blood cells, and whole blood stored in our laboratories from previous studies conducted by our research group (review in Bisso‐Machado et al, 2015; Jacovas et al, ; Salzano, ) using the QIAamp DNA MiniKit (Qiagen, Germany). Samples from non‐Brazilian populations were provided by co‐authors of the present study (JRS and AS‐G).…”
Section: Methodsmentioning
confidence: 99%
“…Even acknowledging the role of genetic drift and other stochastic processes in shaping the genetic diversity of Native Americans (Paixão‐Côrtes et al, ; Tarazona‐Santos et al, ; Wang et al, ), variable selective pressures may partially account for such patterns, including those that have emerged due to new cultural practices (Laland, Odling‐Smee, & Myles, ). Several studies have been conducted based on this premise, some of which demonstrated the action of natural selection in the autochthonous adaptation in the Americas (Acuña‐Alonzo et al, ; Hünemeier et al, ; Foll, Gaggiotti, Daub, Vatsiou, & Excoffier, ; Jacovas et al, ), with others showing negative or contradictory results (Bisso‐Machado, Ramallo, Tarazona‐Santos, Salzano, Bortolini, & Hünemeier, ; Bisso‐Machado et al, ; Demarchi et al, ).…”
Section: Introductionmentioning
confidence: 99%